The modernization of healthcare management in the context of healthcare reform implementation - Shkilniak, Mykhailo; Zheliuk, Tetiana; Vasina, Alla; Dudkina, Olena; Popovych, Tamara; Ovsianiuk-Berdadina, Oleksandra (Herald of Economics, 2019)
*